B cell lymphoma of the thymus and salivary gland. Issue 7 (July 1996) - Di Loreto, C; Mariuzzi, L; De Grassi, A; Beltrami, C A
Abstract : A case of primary low grade B cell lymphoma of the salivary gland associated with a low grade B cell lymphoma of the thymus and involvement of the skin is reported. The lesions in the salivary gland and in the thymus showed the typical features of a lymphoma arising from the mucosa associated lymphoid tissue (MALT) and comprised lymphatic follicles, centrocyte-like (CCL) cells and lymphoepithelial lesions. Immunohistochemistry and Southern blot analysis supported the hypothesis that these lesions can originate from the same cellular clone. These findings confirm the occurrence of low grade B cell MALT lymphoma in the thymus and the possibility of spread of MALT lymphoma to other mucosal sites.